2015
DOI: 10.1128/mcb.00515-14
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis Controls Plasma Membrane Glucose Sensors To Promote Glucose Signaling in Yeasts

Abstract: Sensing of extracellular glucose is necessary for cells to adapt to glucose variation in their environment. In the respiratory yeast Kluyveromyces lactis, extracellular glucose controls the expression of major glucose permease gene RAG1 through a cascade similar to the Saccharomyces cerevisiae Snf3/Rgt2/Rgt1 glucose signaling pathway. This regulation depends also on intracellular glucose metabolism since we previously showed that glucose induction of the RAG1 gene is abolished in glycolytic mutants. Here we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Although the evolved mutant SR8#22 contained no alterations to the Snf3/Rgt2 glucose-sensing pathway, a reduction in the glucose consumption rate was sufficient to induce changes in transporter expression. This observation lends support to previous reports of a link between glycolytic flux and the membrane composition of sugar transporters 28 , 48 . These results indicate that the regulation by the Snf3/Rgt2 pathway on transporter expression can be superseded by a reduction in glycolytic flux.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the evolved mutant SR8#22 contained no alterations to the Snf3/Rgt2 glucose-sensing pathway, a reduction in the glucose consumption rate was sufficient to induce changes in transporter expression. This observation lends support to previous reports of a link between glycolytic flux and the membrane composition of sugar transporters 28 , 48 . These results indicate that the regulation by the Snf3/Rgt2 pathway on transporter expression can be superseded by a reduction in glycolytic flux.…”
Section: Discussionsupporting
confidence: 92%
“…A link between glycolytic flux and regulation of hexose transporters in yeast has been suggested 28 . Furthermore, it has been shown that xylose transport is inhibited by the presence of glucose 14 , 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, in S. cerevisiae and K. lactis glycolytic mutants, glycolysis controls glucose signaling via the SRR pathway. The expression of several glucose-regulated genes, like hexose transporter genes, depends on a functional glycolysis, limiting therefore glucose import (Cairey-Remonnay et al, 2015). However, this control does not seem to exist in C. albicans .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in S. cerevisiae and K. lactis glycolytic mutants, glycolysis controls glucose signalling via the SRR pathway. The expression of several glucose-regulated genes, like hexose transporter genes, depends on a functional glycolysis, limiting therefore glucose import [45]. However, this control does not seem to exist in C. albicans (Fig.…”
Section: Discussionmentioning
confidence: 99%